2014
DOI: 10.4093/dmj.2014.38.3.220
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Health-Related Quality of Life among Saudi Patients with Type 2 Diabetes Mellitus: A Cross-Sectional Survey

Abstract: BackgroundDiabetes mellitus (DM) is associated with high mortality, morbidity, poor general health, and loss of health-related quality of life (HRQOL). The objective of the study was to assess the factors associated with HRQOL among patients with type 2 diabetes mellitus (T2DM).MethodsThis was a cross sectional study conducted among 283 T2DM patients during June 2011 and September 2012 at a major tertiary hospital in Riyadh, Saudi Arabia. The respondents were purposively and conveniently selected according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
101
8
22

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(166 citation statements)
references
References 30 publications
(32 reference statements)
31
101
8
22
Order By: Relevance
“…According to our findings, increasing age was an important risk factor associated with DM in Bisha province, which is in agreement with other reports from other parts of Saudi Arabia (Al Hayek et al, 2014;Amin et al, 2014;Murad et al, 2014) and neighboring countries (Ahmed et al, 2013;Ali, Mehrass, Al-Adhroey, Al-Shammakh & Amran, 2016). Ammarasinghe et al (2015) proposed that geriatric changes in the body systems might invariably contribute to this association.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…According to our findings, increasing age was an important risk factor associated with DM in Bisha province, which is in agreement with other reports from other parts of Saudi Arabia (Al Hayek et al, 2014;Amin et al, 2014;Murad et al, 2014) and neighboring countries (Ahmed et al, 2013;Ali, Mehrass, Al-Adhroey, Al-Shammakh & Amran, 2016). Ammarasinghe et al (2015) proposed that geriatric changes in the body systems might invariably contribute to this association.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, with increasing age, adipose deposition could be increased which might lead to insulin resistance and increasing rates of blood glucose and blood pressure (Amarasinghe et al, 2015). In consistent with other studies in Saudi Arabia (Al-Nozha et al, 2004;Al Hayek et al, 2014;Amin et al, 2014) and in many parts of the world (Soegondo et al, 2011;Soriguer, et al, 2012;Xia et al, 2013;Akter et al, 2014;Amarasinghe et al, 2015), our report revealed that individuals with high body weight were more likely to develop diabetes. Excess body fat well documented as being a risk factor for various chronic conditions such as diabetes, hypertension, hyperlipidemia and cardiovascular diseases (Kamadjeu et al, 2006).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations